Increased Sympathetic Cardiac Autonomic Modulation after Two Consecutive Tilt Tests in Women with Polycystic Ovary Syndrome - Ribeiro, Victor Barbosa; Kogure, Gislaine Satyko; Silva, Rafael Costa; Souza, Hugo Celso Dutra; Ferriani, Rui Alberto; Reis, Rosana Maria dos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective The present study aimed to analyze cardiac autonomic modulation via spectral and symbolic analysis of heart rate variability (HRV) in women with polycystic ovary syndrome (PCOS) who were subjected to two consecutive tilt tests.Methods A total of 64 women were selected and divided into 2 groups: control (without PCOS), and PCOS. Concentrations of follicle-stimulating hormone, luteinizing hormone, prolactin, estradiol, homocysteine, sex hormone-binding globulin, thyroid stimulating hormone, fasting insulin, testosterone, androstenedione, and 17-hydroxyprogesterone levels, triglycerides, free androgen index (FAI), and homeostasis assessment model (HOMA-IR) were assessed. Cardiac autonomic modulation was evaluated by spectral and symbolic analyses during two consecutive tilt tests (two moments) and supine moments before, between and after (three moments) the tilt tests.Results Women with PCOS had higher fasting insulin, HOMA-IR indexes, testosterone and FAI. Additionally, we observed that the PCOS group had greater sympathetic autonomic cardiac modulation in supine 2, tilt 1, and supine 3 moments compared with controls.Conclusion Women with PCOS had higher autonomic sympathetic cardiac modulation even after a second tilt test. No adaptation to this provocative test was observed. Spectral analysis was more sensitive for identifying differences between groups than the symbolic analysis.
Keywords: polycystic ovary syndrome; cardiac autonomic modulation; hyperandrogenism; spectral analysis; symbolic analysis